Chemokines and atherosclerosis: focus on the CX3CL1/CX3CR1 pathway - Apostolakis Stavros; Spandidos Demetrios (Acta Pharmacologica Sinica, 2016)
Atherosclerosis is currently considered an inflammatory disease. Much attention has been focused on the potential role of inflammatory mediators as prognostic/diagnostic markers or therapeutic targets of atherosclerotic cardiovascular disease. CX3CL1 (or fractalkine) is a structurally and functionally unique chemokine with a well documented role in atherosclerosis. In its membrane bound form it promotes the firm adhesion of rolling leucocytes onto the vessel wall, while in its soluble form it serves as a potent chemoattractant for CX3CR1-expressing cells. Additionally, CX3CL1 exerts cytotoxic effects on the endothelium as well as anti-apoptotic and proliferative effects on vascular cells, affecting the context and stability of the atherosclerotic plaque. Studies on animal models have shown that the blockade of the CX3CL1/CX3CR1 pathway ameliorates the severity of atherosclerosis, while genetic epidemiology has confirmed that a genetically-defined less active CX3CL1/CX3CR1 pathway is associated with a reduced risk of atherosclerotic disease in humans. Although several studies support an important pathogenic role of CX3CL1/CX3CR1 in atherogenesis and plaque destabilization, this does not necessarily suggest that this pathway is a suitable therapeutic target or that CX3CL1 can serve as a prognostic/diagnostic biomarker. Further studies on the CX3CL1/CX3CR1 chemokine pathway are clearly warranted to justify the clinical relevance of its role in atherosclerosis.